If Queers were Counted: An Inquiry into European Socioeconomic Data on LGB(TI)QS. - Schönpflug, Karin; Klapeer, Christine M.; Hofmann, Roswitha; Müllbacher, Sandra (Feminist Economics, 2018)
This article is engaged with the public availability, provision, and quality of large-scale data on the socioeconomic standing of lesbian, gay, bisexual, transgender, intersex, and queer persons (LGB[TI]Qs) in Europe. While large-scale data on LGB(TI)Qs are a potentially powerful foundation for public discourse and policymaking, their use and sufficiency are highly contested among researchers, activists, and statistical bodies. Analyzing data provided by official national and European statistics institutes, this article describes the inclusion of sexual orientation in the data-generation and reporting processes in thirty European countries and discusses how legal and social acknowledgment make LGB(TI)Qs in/visible in socioeconomic statistics. The article therefore examines if and how LGB(TI)Qs are being “counted” and, importantly, what it means “if queers are counted.”